2005
DOI: 10.1007/s11738-005-0029-z
|View full text |Cite
|
Sign up to set email alerts
|

Doubled haploids in production of male sterility maintaining triticale (Triticosecale Wittmack) lines

Abstract: Plant Breed ing and Ac cli ma ti za tion In sti tute, Radzików, 05-870 Błonie, Po land * Uni ver sity of Tech nol ogy and Ag ri cul ture, Ab stractThe androgenetic re sponse of sev eral se lected male ste ril itymaintainer ge no types of triticale was in ves ti gated. Androgenesis in duc tion was ob tained in all cultivars, but a large genotypic vari a tion in green plant re gen er a tion was ob served. The num ber of re gen er ated triticale plants var ied from 0.1 to 4.7 green plants per spike, de pend ing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…Without chlorophyll, the primary pigment involved in light harvesting and its transformation into chemical energy, albinotic plants cannot survive in natural environment, and do not represent any agronomic value. Tuvesson et al (2003) reported that albino plantlets have outnumbered green regenerants 2.6-fold, whilst in other studies, albinos have represented 42 % of all regenerated plantlets (Warzecha et al 2005). In the main experiment presented, the mean number of regenerating AS gained 18.5 % with the frequency of albino plants at about 53 %.…”
Section: Discussionmentioning
confidence: 69%
“…Without chlorophyll, the primary pigment involved in light harvesting and its transformation into chemical energy, albinotic plants cannot survive in natural environment, and do not represent any agronomic value. Tuvesson et al (2003) reported that albino plantlets have outnumbered green regenerants 2.6-fold, whilst in other studies, albinos have represented 42 % of all regenerated plantlets (Warzecha et al 2005). In the main experiment presented, the mean number of regenerating AS gained 18.5 % with the frequency of albino plants at about 53 %.…”
Section: Discussionmentioning
confidence: 69%
“…Twelve F 1 hybrids of winter hexaploid triticale were used ( Androgenesis protocols were the same as routinely used for microspore culture (Oleszczuk et al 2004) and anther culture (Warzecha et al 2005) of triticale. Tillers were cold-treated in water for 4 weeks.…”
Section: Androgenesis and Plant Regenerationmentioning
confidence: 99%
“…These lines were TG 5B, TG Dt5BL, and TG 5B + 5BL where Dt stands for ditelocentric. Plants of these lines were grown in the greenhouse at the IHAR in Radzikow, Poland, and all procedures of material collection, storage, plating, and anther culture conditions were standard as described for triticale [Warzecha et al, 2005] and often used for rye. For each line, anthers from 30 heads were plated which amounted to ca.…”
Section: Methodsmentioning
confidence: 99%